PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA KARYAWAN PT. TIRTA INVESTAMA DANONE AQUA SEMARANG) - Libina Patricia; Dinalestari Purbawati (Universitas Diponegoro, 2020)
The increasingly fierce competition between e-commerce makes the company need to increase the consumers satisfaction through product quality and service quality, so they can survive and continue to get profits. This research was conducted with the aim of examining the effect of product quality and service quality through consumer satisfaction at Lazada.This research is quantitative research that uses explanatory type. Sampling technique uses non probability sampling and purposive sampling approach. Where the population is all Lazada consumers in Universitas Diponegoro Semarang, while the sample is 100 Lazada consumers with certain criteria carried out. Data collection techniques using google form and interviews.The analysis used in this study is linear regression analysis using SPSS 21.0 for Windows. The results of this study indicate that product quality and service quality have a significant effect on customer satisfaction.Based on the results of research Lazada must increase consumer satisfaction by increasing product quality through product durability, quality of the product packaging and more careful on processing order so the ordered product will match with the one that consumer accept. In addition Lazada also needs to notice quality service for more responsive in serving consumer and faster in giving solution on consumer complaint, also strive for timely delivery of goods estimated. So that it will increase consumer satisfaction at Lazada.